Indian Cattle / Cattle Stealing / Cattle - Joseph McCoy (Symphony in the Flint Hills, 2017)
Introduction: What did a Scot-Cherokee trader and a college educated easterner have in common? Ties to the region’s first source of marketable beef cattle.
Keywords: American Indians; cattle ranchers; Cherokee; Jesse Chisholm